Exploring Collaborative Problem Solving in STEM Contexts for Middle School Students - Dewi, Tiara Rahma Putri Kusuma; Hidayat, Dayat; Milla, Yulia Izza El (Universitas Negeri Surabaya, 2023)
In the 21st century, advances in science and technology require students to adapt. Classroom dynamics are still often dominated by passive learning methods, such as lectures, which result in a lack of student participation. PISA evaluation shows the low problems-solving abilities of Indonesian students. Therefore, the STEM approach emerged as a solution with a focus on essential 21st century skills, such as collaborative problem solving. The aim of the research is to investigate and analyze the collaborative problem solving process of junior high school students in solving STEM problems. The research method used is a case study with a qualitative approach. The research population included all students of SMP PGRI 13 Surabaya. Data collection techniques include observation, interviews, and questionnaires. Research instruments include questionnaires, observation sheets, and structured interviews. The research results show that collaborative learning in STEM context problem solving can help students develop problem solving skills. Students demonstrate good collaborative skills and their response to this learning is very positive. Evaluation of student learning outcomes also shows an increase, indicating the success of STEM-based learning methods in increasing student motivation. This research contributes to the understanding of the importance of learning approaches that integrate STEM with collaborative problem solving.